Metode Simple Multi-Attribute Rating dalam Seleksi Kelayakan Penerima Bantuan Sosial di Perkumpulan Wanita Tabita - Hutagalung, Bambang TJ; Siregar, Elida Tuti (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
Tabita Women's Society faces obstacles in determining objective criteria in selecting congregations of social aid recipients who are economically disadvantaged as a result of the limited social assistance available. This is due to the absence of a measurable system in determining the recipient of social assistance. To facilitate the selection of social assistance recipients, there needs to be a system that is able to provide results in the form of output that is the most eligible recipient of social assistance in receiving social assistance. The criteria for the selection of social assistance recipients refers to the fulfillment of several elements, namely: monthly income, age, number of dependents, status of residence, marital status, disability, and participants of PKH (Hope Family Program). The method used in this study is the SMART (Simple Multi-Attribute Rating Technique) method. The results showed that the use of SMART methods is effective in determining the citizens of the congregation who are most worthy of social assistance so as to create a sense of fairness, objectivity, and transparency in making decisions to the entire congregation.